Improvements in goal-oriented learning through game activity and its development in motor skills - Arias Macias, Lissette Estefania; Vargas Vera, Ana Elizabeth (SPORT TK-EuroAmerican Journal of Sport Sciences, 2024)
Goal-oriented play activity encourages children to exercise and triggers body muscle movement. Active muscles are stronger, more agile, faster and more powerful. The purpose of this study is to determine that goal-oriented play activity in early childhood improves motor skills. Forty children aged 6 to 7 years were recruited and participated in a set of training activities divided into positions 1 to 5. To pass each pole, a child had to run, walk on a balance beam, swing sticks, throw and catch the ball, and arrange blocks. Training was given three times a week for 12 weeks. The data collected consisted of running 25 m, walking on the balance beam, throwing the ball as far as possible, locomotor movement, organizing cans, and bouncing the ball. Paired t tests and Wilcoxon signed ranks were used for analysis. The results showed that there were significant differences in the motor skills evaluated pre and post training with p < 0.05. The six training activities conducted over 12 weeks provided significant improvements in motor skill areas in children aged 6 to 7 years.